How to interpret post-concussion symptom severities of scat3 in professional ice hockey players. Issue 11 (25th May 2017) - Hänninen, Timo; Parkkari, Jari; Tuominen, Markku; Iverson, Grant L; Vartiainen, Matti; Öhman, Juha; Luoto, Teemu M
Abstract : Objective: To characterise the baseline to post-concussion variation of each SCAT3 symptom. Design: Prospective cohort. Setting: Finnish professional ice hockey league. Participants: SCAT3 baseline testing has been mandatory in the Finnish hockey league since 2013. The league recommends day of injury testing for all players with suspected concussion. Of the reported day of injury SCAT3s, between seasons 2013–2016, a total of 29 concussions were confirmed by the teams' medical staff. Intervention: Outcome measures: The day of concussion symptom severities for each of the 22 symptoms were compared to (i) the league's normative reference values [based on 2013–2014 preseason baselines (n=270)] and (ii) the baseline scores of the 29 concussed players. The change between day of concussion score and players' individual baseline score was compared to: (i) the reference variation of the league's two preseason baselines [2013–2014 and 2014–2015 (n=179)], and (ii) the variation between two preseason baselines of the concussed players. Main results: The most prevalent post-concussion symptoms were: "Don't feel right" (100%), headache (97%), and pressure in the head (90%). In addition, these symptoms were the most common to worsen on the day of concussion compared to players' individual baseline. "Feeling like in a fog", confusion, and dizziness were common on the day of injury (each reported by 72%) but rare on baselines (1–2%). Fatigue or low energy and neck pain were the most common and unstable baseline symptoms in the league. Conclusions: Headache and "Don't feel right" were the most useful symptoms on the SCAT3 in acute concussion recognition. Competing interests: None. Timo Hnninen, Jari Parkkari, Markku Tuominen, Matti Vartiainen, Juha hman, Teemu M. Luoto: None. Grant L. Iverson has been reimbursed by the government, professional scientific bodies, and commercial organisations for discussing or presenting research relating to mild TBI and sport-related concussion at meetings, scientific conferences, and symposiums. He has a clinical and consulting practice in forensic neuropsychology involving individuals who have sustained mild TBIs (including professional athletes). He has received research funding from several test publishing companies, including ImPACT Applications, Inc., CNS Vital Signs, and Psychological Assessment Resources (PAR, Inc.). He has not received research support from a test publishing company in the past 5 years.